PENINGKATAN KETERAMPILAN PROSES IPA MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH DI KELAS IV SEKOLAH DASAR - wati, erna (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Improvement  of Science Process Skill  through a Problem-Based Learning Model  for the  4th Grade  Students of Elementary School. The aims of the research to increase the skill of science process of the 4th grade students of elementary school by applying the problem-based learning model. The method of this research can be categorized as a collaborative classroom action research (CAR) conducted in three cycles; every cycle consists of plan, the execution of  action, observation, and reflection. The research subjects totalling 20 students of elementary school. The data analysis was done qualitatively and quantitatively. The result of the research showed that the problem-based learning model can improve the skill of science process of the 4th grade students. The conclusion of the research is the problem-based learning model can improve the skill of science process of the 4th grade students of elementary school. Keywords: the problem-based learning model, the skill of process, science   Abstrak: Peningkatan Keterampilan Proses IPA melalui Model Pembelajaran Berbasis Masalah di Kelas IV Sekolah Dasar. Tujuan penelitian ini adalah meningkatkan keterampilan proses IPA pada siswa kelas IV sekolah dasar melalui model pembelajaran berbasis masalah. Metode penelitian ini adalah Penelitian Tindakan Kelas (PTK) kolaboratif yang dilaksanakan dalam tiga siklus, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian adalah siswa kelas IV sekolah dasar yang berjumlah 20 siswa. Hasil penelitian menunjukan bahwa model pembelajaran berbasis masalah dapat meningkatkan keterampilan proses IPA pada siswa kelas IV. Simpulan penelitian adalah model pembelajaran berbasis masalah dapat meningkatkan keterampilan proses IPA pada siswa kelas IV sekolah dasar.   Kata Kunci: model pembelajaran berbasis masalah, keterampilan proses, IPA